“My work opportunities depend on how much I can take” : inappropriate behaviour and harassment in the cultural domain in Finland - Jaakola, Meri (2022)
Phenomena of inappropriate behaviour and harassment are neither new nor unique to the cultural domain. However, these phenomena have not been largely publicly discussed before the 2017 me too movement, presumably due to the culture of silence prominent within the cultural domain. After the movement that started from the film industry and quickly spread around the world, discussion on ethical working conditions has arisen within all the cultural domain as well. This qualitative driven mixed methods research reviews the current situation of inappropriate behaviour and harassment in Finland and seeks to understand the magnitude and forms of the phenomena. The research questions are: 1) What special characteristics or structures in the arts and culture field enable inappropriate behaviour and harassment or the possibility of them? And 2) What can be done to eliminate inappropriate behaviour and harassment from arts and culture workplaces? The research questions are answered analyzing research data collected using a survey and six themed interviews. Research data was collected in the spring of 2021. Topics that surfaced from the survey were used as a basis for the interview questions. Findings from the survey and the interviews act as the thematical scope of this master’s thesis, as they are the most important themes to come out of this research. The main findings of the thesis are that there are four elements that enable and maintain the improper working culture within the cultural domain. The elements are insufficient funding, poor management, artist myth, and limitlessness of the work. These themes are examined in discussion with literature. The four steps this thesis suggests helping uproot the improper behaviour in the cultural domain according to the research data and literature are 1) Pushing for the cultural domain’s ethical board to be established, 2) Composing ethical guidelines for all the cultural domain, 3) Basing funding on following the said guidelines, and 4. Talking about improper behaviour publicly and bringing cases of misconduct forward.

Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam